2016
DOI: 10.1063/1.4961019
|View full text |Cite
|
Sign up to set email alerts
|

The near-infrared spectrum of ethynyl radical

Abstract: Transient diode laser absorption spectroscopy has been used to measure three strong vibronic bands in the near infrared spectrum of the C 2 H, ethynyl, radical not previously observed in the gas phase. The radical was produced by ultraviolet excimer laser photolysis of either acetylene or (1,1,1)-trifluoropropyne in a slowly flowing sample of the precursor diluted in inert gas, and the spectral resolution was Doppler- (2004)), the vibronic character of these levels was also assigned. The observed states conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…In total, 77 transitions from rotational levels in theX(0, 1 1 , 0) 2 Π state to those in the previously observed [9] 2 Σ state at 7088 cm −1 were identified via lower state combinational differences, initially using the constants reported by Hsu et al [14] The upper state in this transition suffers strong perturbations that were identified in the earlier work. [9] We have combined all the published high precision spectroscopic data for the lowerX(0, 1 1 , 0) 2 Π level in a weighted least squares fit to the lower state constants.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In total, 77 transitions from rotational levels in theX(0, 1 1 , 0) 2 Π state to those in the previously observed [9] 2 Σ state at 7088 cm −1 were identified via lower state combinational differences, initially using the constants reported by Hsu et al [14] The upper state in this transition suffers strong perturbations that were identified in the earlier work. [9] We have combined all the published high precision spectroscopic data for the lowerX(0, 1 1 , 0) 2 Π level in a weighted least squares fit to the lower state constants.…”
Section: Discussionmentioning
confidence: 92%
“…Details of the spectrometer used here have been given previously. [9] A Sacher Lasertecknik tunable diode laser, model TEC 500, with output centered at 1450 nm was used to record Doppler-limited spectra between 6600 and 6900 cm −1 , following 193 nm ArF excimer laser photolysis of 3,3,3 trifluoropropene, CF 3 C 2 H, as a source of C 2 H. For most of the work, a dual beam setup was employed to reduce laser source noise and the signal and reference beams were imaged on to the elements of an a.c.-coupled dual InGaAs photoreceiver (New Focus 1617). A spectrum was obtained by averaging 40 (typically) photolysis laser shots per wavelength step of, normally, 0.005 cm −1 in a 1:1 mixture of CF 3 C 2 H and argon at a total pressure of 1.0 Torr with a detection time gate of 1.0 µs starting at either zero time delay following the photolysis or after few µs of delay time to allow for partial collisional relaxation of the initially hot sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The OH radical kinetics reported here were measured inside a Herriott‐type slow flow reactor using FM laser absorption spectroscopy. This technique and apparatus have been described in detail elsewhere . Briefly, gas flows of nitric acid (HNO 3 ), C 2 H 4 and argon were regulated using calibrated mass flow controllers and flowed into a 2‐m glass Herriott‐type flow tube.…”
Section: Methodsmentioning
confidence: 99%
“…This technique and apparatus have been described in detail elsewhere. 43,[50][51][52]55,56 Briefly, gas flows of nitric acid (HNO 3 ), C 2 H 4 and argon were regulated using calibrated mass flow controllers and flowed into a 2-m glass Herriott-type flow tube. The total pressure inside the flow tube was controlled by adjusting a throttling valve on the exhaust line to a liquid nitrogen-trapped rotary pump (Pfeiffer, PK D56 112), and measured using capacitance manometers (MKS, 622c; Edwards, 600 AB).…”
Section: Methodsmentioning
confidence: 99%